RANCANG BANGUN SINKRONISASI PEWAKTUAN LAMPU LALU LINTAS MENGGUNAKAN PLC OMRON CPM2A DAN WONDERWARE INTOUCH - , SYUKRI HADI KAMIL P; , Andi Dharmawan, S.Si., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A Research has been carried out with the title Traffic Lights Timing Synchronization Design Using PLC Omron CPM2A And Wonderware InTouch. The system is intended to make vehicles no need to wait for green light at the next intersection after clearing an intersection before. An intersection received a signal from previous intersection in order to adjust the timing of its signal so the objective above can be achieved. Speed of vehicles and the distance between intersection is the main factor for synchronization system. The distance is entered manually into the system. Vehicles speed can be calculated with two sensors mounted on the road. When the synchronization signal is received, depending on the color of the lights were lit, active synchronization types can be divided into six types . Each type has itâs timing calculations for synchronization. The use of the synchronization system is able to avoid the vehicle hit a red light at the synchronized intersection in real time on a prototype is 24 times out of 30 attempts (80%) with an average waiting time when hitting the red light is 12,02 seconds, while in the simulation is 17 times out of 30 attempts (56,67%) with an average waiting time when hitting the red light is 1,25 seconds. Recommended maximum vehicle speed in theory on simulation is 46,67 km/h.